2016
DOI: 10.1111/1365-2664.12643
|View full text |Cite
|
Sign up to set email alerts
|

The importance of realistic dispersal models in conservation planning: application of a novel modelling platform to evaluate management scenarios in an Afrotropical biodiversity hotspot

Abstract: Summary As biodiversity hotspots are often characterized by high human population densities, implementation of conservation management practices that focus only on the protection and enlargement of pristine habitats is potentially unrealistic. An alternative approach to curb species extinction risk involves improving connectivity among existing habitat patches. However, evaluation of spatially explicit management strategies is challenging, as predictive models must account for the process of dispersal, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…When such links are made, it is possible to gain important new insights into the dynamics of species living on complex landscapes and into potential consequences of alternative management interventions [215]. In one recent example, [216] used RangeShifter to combine a stochastic IBM for movement with a spatially explicit population model to explore alternative plausible management scenarios for birds in the Taita Hills in Kenya, a biodiversity hotspot. The results demonstrated that while adding new habitat patches boosted overall population abundance, potential risks exist of placing them in certain locations that may represent Bdisperser sinks^, effectively halting dispersers that would otherwise have immigrated into other existing patches and, therefore, reducing abundance in those existing patches.…”
Section: Process-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…When such links are made, it is possible to gain important new insights into the dynamics of species living on complex landscapes and into potential consequences of alternative management interventions [215]. In one recent example, [216] used RangeShifter to combine a stochastic IBM for movement with a spatially explicit population model to explore alternative plausible management scenarios for birds in the Taita Hills in Kenya, a biodiversity hotspot. The results demonstrated that while adding new habitat patches boosted overall population abundance, potential risks exist of placing them in certain locations that may represent Bdisperser sinks^, effectively halting dispersers that would otherwise have immigrated into other existing patches and, therefore, reducing abundance in those existing patches.…”
Section: Process-based Modelsmentioning
confidence: 99%
“…For smaller numbers of species we can reasonably expect to be able to acquire the data to parameterise this extra complexity. Recent work has used IBMs that incorporate current landscapes to inform the choice between alternative options for landscape management targeting birds in fragmented forests [216] to inform the design of reintroduction or assisted colonisation strategies [257] and to determine how alternative possible management options for UK forests will facilitate the range shifting of species [19]. However, there are a lack of studies that consider how these conservation strategies will fare in the context of dynamically changing landscapes and thus using the IBMs with pattern-based models that provide spatio-temporal projections of landscapes would be a particularly valuable direction to pursue.…”
Section: Study Population Viability Under Future Scenarios Using Ibmsmentioning
confidence: 99%
“…The Mediterranean region has been affected by anthropic disturbances for thousands of years, and is, today, one of the most significantly altered hotspots in the world, with Italy following this general trend (Dalla Valle et al, 2009;Niedertscheider and Erb, 2014;Pelorosso et al, 2009;Shelef et al, 2016). Concurrently, the Mediterranean hotspots, similarly to other sites of biodiversity, are characterized by high human population densities (Aben et al, 2016). In the last 40 years, a particular pattern of land-use/land-cover change has taken place in the Mediterranean basin, especially in Mediterranean Europe and Italy: plains are being increasingly used; hilly and mountain areas are being abandoned by humans and naturally reforested; and human settlements are quickly increasing along the coastline, with the resident population doubling every 30 years and tourists' presence doubling every 15 years (Falcucci et al, 2007;Lambin et al, 2001Lambin et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution models can help scientists and conservation planners estimate centres of biodiversity (Barthlott et al, 2005;Brotons et al, 2004) and identify priority areas for conservation (Elith and Leathwick, 2009) as well as patterns of major threats across the landscape, such as habitat loss, fragmentation and other anthropogenic pressures (e.g., Aben et al, 2016;Ibáñez et al, 2009;Newbold et al, 2016). In contrast, one dilemma with mapping concerns which species should be evaluated because it is impossible to map them all (Miller and Allen, 1994;Mittermeier et al, 2004;Trisurata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation models of woodland and forest dynamics require an understanding of the seed production and dispersal processes that determine the landscape distribution of tree populations (Aben et al., ). We assembled and parametrized a process‐based model that captured population dynamics as well as plant–animal interactions of Q. pacifica , a keystone species targeted for restoration efforts in the Channel Islands National Park.…”
Section: Discussionmentioning
confidence: 99%